Optimización de la producción de la industria láctea PASTOLAC a partir del uso del subproducto y desecho. - Maya Mesias, Julio César (2018)
Whey is a byproduct that is obtained by the precipitation of casein in the cheese production, contains more than 50% of milk solids where proteins, fats, minerals and vitamins are found. For many years it was considered a waste and a contaminating substance, but this perspective has changed because it is a source rich in raw materials and each of the elements that compose it can be exploited in different ways. Whey proteins are being used in food functions as formulas to combat malnutrition in children, protein shakes used by athletes, among the most relevant uses. This research project seeks to establish a new use for whey derived from the cheese production. It is considered that the whey is a very important problem in the cheese industry, this has a high ecological and economic impact. With the objective of developing protein concentrates to avoid the continued wasting of their nutritive properties and contaminating the environment, the decision was made to prepare a pilot plant for protein concentrate, since there is no single process for its preparation. To carry out this process, It has been used an ultrafiltration system using membranes, initially carrying out a filtration to reduce the fat content, and later, an ultrafiltration with molecular cutting membranes. In the ultrafiltration process the protein molecules are of a size that do not pass through the pores of the molecular cut membranes, for this reason this method of obtaining protein concentrate was chosen, being the most efficient method to obtain the as much as possible to the whey, generating a profit not only environmental but also economic to the company PASTOLAC. The pilot plant proposed in this research work is structured according to the needs of the PASTOLAC company, so that it can work effectively and efficiently, generating only benefits.